Impact of the Novel CoronaviruS (COVID-19) on Frontline PharmacIsts Roles and ServicEs: INSPIRE Worldwide Survey - Kaitlyn E. Watson; Dillon H. Lee; Mohammad B. Nusair; Yazid N. Al Hamarneh (MDPI AG, 2023)
Background: Pharmacy has been recognized as a vital healthcare profession during the COVID-19 pandemic. The primary objective of the INSPIRE Worldwide survey was to determine the impact of COVID-19 on pharmacy practice and pharmacists' roles around the world. Methods: A cross-sectional online questionnaire with pharmacists who provided direct patient care during the pandemic. Participants were recruited through social media, with assistance from national and international pharmacy organizations between March 2021-May 2022. The questionnaire was divided into (1) demographics, (2) pharmacists' roles, (3) communication strategies, and (4) practice challenges. The data were analyzed using SPSS 28, and descriptive statistics were used to report frequencies and percentages. Results: A total of 505 pharmacists practicing in 25 countries participated. The most common role that pharmacists undertook was responding to drug information requests (90%), followed by allaying patients' fears and anxieties about COVID-19 (82.6%), and addressing misinformation about COVID-19 treatments and vaccinations (80.4%). The most common challenges were increased stress levels (84.7%), followed by medication shortages (73.8%), general supply shortages (71.8%), and inadequate staffing (69.2%). Conclusions: Pharmacists within this study were significantly impacted by the COVID-19 pandemic and took on new or adapted roles (e.g., providing COVID-specific information, managing patients' emotions, and educating on public health measures) to meet the needs of their communities. Despite, the significant challenges (e.g., increased stress, supply chain challenges, addressing misinformation, and staffing shortages) faced by pharmacists, they continued to put their patients' needs first and to provide pharmacy services.